Review of Cervical Cancer Preventive and Screening Strategies in India - Meena, Devi; Chand, Subhash; Kumar, Deovrat (Asian Journal of Pharmaceutical Research and Development, 2019)
Cervical cancer (CC) rapidly spread in the women. CC is the cancer which start from the cervix this is the 1st stage and 3rd most common type cancer in women’s worldwide. Continuously, Human papillomavirus (HPV) infection is the higher&strongest epidemiologic risk factor for CC.HPV-16 and HPV-18, these are type virus with high-risk HPV types. But at present many types of techniques available as – Pap smear test, Colposcopy, HPV virus test/detection, Visual inspection of cervix with 5% acetic acid, and Visual inspection of cervix with Lugol’s Iodine.The majority of diagnosis with CC will be analyzed more than 13000 and rate of death 4000 with women in United States and it also deadline disease in India. It is one of the cancer which is preventable. This article studied with in PubMed and Google scholar, studies about cervical cancer from Wikipedia and you-tube also. And it is only meta-analysis or multi-institutional, review article and research studies were considered for analysis of cervical cancer. The most important risk factor is determined with human beings Human papillomavirus (HPV) which traditional in worldwide. This is the type of cancer which is screening and detect in the early stage by the screening methods. In this article, abstracted published studies about to year between during 1995-2018 which has been carried out in worldwide on CC with significance on screening test methods. Basically, Pap smear is the method of screening for cytology but now a day many studies have been accomplish to investigate different methods as well as visual inspection method. Keywords: Cervical Cancer screening, HPV, Screening methods, Pap Smear test, India United State.